N6-methyladenosine modification in 18S rRNA promotes tumorigenesis and chemoresistance via HSF4b/HSP90B1/mutant p53 axis. Issue 2 (16th February 2023) - Chen, Binbin; Huang, Ying; He, Shuiqing; Yu, Peng; Wu, Lirong; Peng, Hao
Summary: Aberrant N 6 -methyladenosine (m 6 A) modification on mRNA is correlated with cancer progression. However, the role of m 6 A on ribosomal RNA (rRNA) in cancer remains poorly understood. Our current study reveals that METTL5/TRMT112 and their mediated m 6 A modification at the 18S rRNA 1832 site (m 6 A1832 ) are elevated in nasopharyngeal carcinoma (NPC) and promote oncogenic transformation in vitro and in vivo . Moreover, loss of catalytic activity of METTL5 abolishes its oncogenic functions. Mechanistically, m 6 A1832 18S rRNA modification facilitates the assembly of 80S ribosome via bridging the RPL24-18S rRNA interaction, therefore promoting the translation of mRNAs with 5′ terminal oligopyrimidine (5′ TOP) motifs. Further mechanistic analysis reveals that METTL5 enhances HSF4b translation to activate the transcription of HSP90B1, which binds with oncogenic mutant p53 (mutp53) protein and prevents it from undergoing ubiquitination-dependent degradation, therefore facilitating NPC tumorigenesis and chemoresistance. Overall, our findings uncover an innovative mechanism underlying rRNA epigenetic modification in regulating mRNA translation and the mutp53 pathway in cancer. Graphical abstract: Highlights: m 6 A1832 facilitates the assembly of 80S ribosome via RPL24-18S rRNA bridge m 6 A1832 18S rRNA modification selectively regulates the translation of 5′TOP mRNAs METTL5 inhibits ubiquitin-dependent degradation of p53 R280T via HSF4b/HSP90B1 axis METTL5 promotes tumorigenesis and chemoresistance via gain-of-function p53 R280T Abstract : Chen et al. show that METTL5/TRMT112-mediated m 6 A1832 18S rRNA modification selectively regulates the translation of 5′TOP mRNAs via bridging the RPL24-18S rRNA interaction. Moreover, METTL5 promotes tumorigenesis and chemoresistance via the HSF4b/HSP90B1/p53 R280T axis. Altogether, this study uncovers an innovative RNA epigenetic mechanism in cancer.